Prospects of Payment for Ecosystem Services: Case from Water Service Scheme in Nepal - Dhakal, Kunju; Bhattarai, Sushma; Dhakal, Benju (FORESTRY: Journal of Institute of Forestry, Nepal, 2021)
Payment for ecosystem services (PES), a voluntary transaction for the optimum use of scarce natural resources, are highly recommended for conservation of forests and watershed. Despite multiple recommendations, there has not been enough studies regarding PES in Nepal, except for limited areas like hydropower plants and community forests. Every PES scheme is unique, depending upon the conditions prevalent in its site therefore more studies are required to understand appropriateness of PES mechanism. Taking drinking water scheme in Sundarijal watershed as a case, this study assessed drinking water supply scheme prevalent in the site, and prioritized its problems, and expectations, from stakeholders’ perspectives. A phenomenological cross-sectional research approach was used and data were collected through in-depth interviews with major stakeholders. The result transcripts were analyzed in Atlasti version 7 and prioritized based on their frequency. The proper buying and selling mechanisms were not found in the current drinking water supply scheme in Sundarijal. The poor economic condition of users, inadequate funds in water users committee, and inadequate water collection for sales were determined as primary obstacles associated with PES establishment at the study site. Since the area has immense potential for PES, building additional water collection tanks with filter plants, a collaboration of multiple local organizations in the preparation of baseline document, identification of additional water sources, and adequate funding are perquisite to establish proper payment mechanism.